Biomass, Biopolymer-Based Materials, and Bioenergy 2019
DOI: 10.1016/b978-0-08-102426-3.00018-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of biodiesel from rice bran oil

Abstract: Rice bran is a byproduct of the milling process of paddy rice to produce refined rice. Rice bran oil (RBO) is a valuable domestic oil resource in many countries, its acceptability as an edible oil has been hampered because of its commonly high free fatty acid (FFA) content resulting from the high lipase activity of the bran. Depletion in nonrenewable sources, especially for petroleum diesel and fossil fuel, has alarmed the global community into looking for an alternative way to overcome this situation. One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The production of biodiesel from rice bran is actively marketed all over the globe. However, rice bran oil must be removed from the rice bran to produce biodiesel via a transesterification process [152]. Several methods have purportedly been utilized to produce biodiesel from rice bran oil, including acid-catalyzed and base-catalyzed transesterification and lipase-catalyzed transesterification.…”
Section: Valorization Of Rice Branmentioning
confidence: 99%
“…The production of biodiesel from rice bran is actively marketed all over the globe. However, rice bran oil must be removed from the rice bran to produce biodiesel via a transesterification process [152]. Several methods have purportedly been utilized to produce biodiesel from rice bran oil, including acid-catalyzed and base-catalyzed transesterification and lipase-catalyzed transesterification.…”
Section: Valorization Of Rice Branmentioning
confidence: 99%
“…The existence of a functional lipase enzyme within RBO results in a significantly higher concentration of free fatty acids (FFA) compared to the bran oil derived from other cereal grains. Therefore, it may be concluded that a significant proportion, approximately 60-70%, of the RBO is deemed unfit for eating, particularly in relation to its use in food products [26]. The prospect of converting non-edible rice bran oil (RBO) into biodiesel has drawn significant attention for the generation of RBO's volumes [27,28].…”
Section: Background Of Studymentioning
confidence: 99%
“…Zaidel et al [86] discussed in their review study the production of biodiesel from rice bran oil. The authors reported the use of methanol as the reaction alcohol.…”
Section: Rice Bran Vegetable Oilmentioning
confidence: 99%